Effect of annealing on the physico-chemical properties of rice starch and the quality of rice noodles. (November 2018) - Wang, Li; Zhang, Congnan; Chen, Zhengxing; Wang, Xiaopei; Wang, Kang; Li, Yongfu; Wang, Ren; Luo, Xiaohu; Li, Yanan; Li, Juan
Abstract: The effects of annealing treatment on the properties of rice starch and the quality of rice starch noodles was studied. The results demonstrate that annealing did not change the granule morphology or the crystalline pattern of the rice starch but the relative crystallinity increased from 19.18% to 23.93%. Compared to native rice starch, the solubility and swelling power of annealed rice starch decreased significantly ( P < 0.05) to 14.35% and 10.09 g/g, respectively. In addition, annealed rice starch had remarkably (P < 0.05) lower values of pasting viscosity, breakdown and setback. Apparent changes in the gel texture of rice starch were also observed, and these changes helped improve the qualities of the rice starch noodles. Furthermore, with increasing annealed rice starch content in the blends, the sensory evaluation scores, cooking qualities and texture properties of rice starch noodles increased gradually. When 40% (w/w) of the native rice starch was substituted with annealed rice starch, the resulting noodles had the best overall qualities. Additionally, the properties of rice starch showed good correlation with the qualities of rice starch noodles, so these properties could be practical indicator for suitability of a starch substrate for noodles. Highlights: Annealing treatment reduces the swelling power and solubility of rice starch. Annealing treatment reduces the paste viscosity of rice starch. Annealing treatment improves the gel texture properties of rice starch. Annealing treatment improves the cooking and sensory qualities of rice starch noodles. Annealing treatment improves the texture properties of rice starch noodles.